The mental health of medical students during the COVID-19 pandemic: a literature review. - Fedotova Зоя; Abdrjahimova Цира; Kleban Катерина (Psychosomatic Medicine and General Practice, 2023)
Introduction Viral diseases have been a severe problem at the global level, gaining more or less publicity from time to time. At the end of 2019, the world witnessed alarming news about the spread of the coronavirus disease (COVID-19) across the globe. The speed of spread and severity of complications from COVID-19 have made it a global threat. Researchers indicate that the COVID-19 pandemic may cause mental trauma globally [1]. That is why the mental health of doctors and medical students is becoming increasingly important. At the same time, it becomes clear that this area needs further research and interventions[2]. In 1948, WHO defined health as complete physical, mental, and social well-being. And if, for physical well-being, society can get help by turning to somatic profile doctors, then seeking help, in case of mental illness, is still considered a stigma in society. Mental illness is highly stigmatized, and it is becoming increasingly clear that this stigma is widespread within the general population and among medical professionals and students [3,4]. Previous literature dating back to 2019 suggests that the process and conditions of medical university education represent a set of stressors that may contribute to the development of mental illness[5,6,7]. Despite the increased interest of the scientific community in this topic, unified protocols of prevention and care to overcome these problems still need to be developed. With the beginning of the pandemic, the question of the mental health of medical students arose repeatedly and urgently. Thus, further research on the mental health of medical students and the systematization of knowledge gained before and during the pandemic is needed. This review article aims to systematize information on the mental health of medical students to outline the next steps in solving this issue. We have analyzed the literature on the topic published during the last five years. For a literature search, such databases as PubMed, APA PsychNet, Google Scholar, Scopus, and Web of Science were used. The number of publications on students’ mental health increased, and with the beginning of the pandemic, it peaked (Fig. 1), indicating the extreme relevance of this topic.